Climatic and Ecological Change in the Americas A Perspective from Historical Ecology - Whitaker, James Andrew; Armstrong, Chelsey Geralda; Odonne, Guillaume (New Frontiers in Historical Ecology, 2024)
This book offers a comparative analysis of the experiences, responses, and adaptations of people to climate variability and environmental change across the Americas. It foregrounds historical ecology as a structural framework for understanding the climate change crisis throughout the region and throughout time. In recent years, Indigenous and local populations in particular have experienced climate change effects such as altered weather patterns, seasonal irregularities, flooding and drought, and difficulties relating to subsistence practices. Understanding and dealing with these challenges has drawn on peoples' longstanding experience with climate variability and in some cases includes models of mitigation and responses that are millennia old. With contributions from specialists across the Americas, this volume will be of interest to scholars from fields including anthropology, archaeology, geography, environmental studies, and Indigenous studies.